Cambodia Economic Update, April 2014 : Coping with Domestic Pressures and Gaining from a Strengthened Global Economy - World Bank (Phnom Penh, 2014)
Cambodia's economy has withstood domestic pressures and managed to sustain its high growth driven by its usual engines of growth. The external sector improved as a result of slower imports due to dampened domestic demand. The post-election adverse effects slowed down the demand for imports, while export growth advanced. Inflation rose to 4.7 percent year-on-year at the end of 2013, up from 2.5 percent at the end of 2012. Inflation is projected to remain in mid-single-digits over the short term. Financial deepening continues but the gap between credit and deposit growth rates has widened, reducing bank liquidity. Government revenue growth has moderated, resulting in an increase in the fiscal deficit. The latest joint World Bank and International Monetary Fund (IMF) debt-sustainability analysis (DSA) conducted in 2013 shows that Cambodia's debt-distress rating remains low, with all debt-burden indicators projected to be below respective thresholds. The prospects for sustaining high growth appear favorable, and real growth for 2014 is projected to reach 7.2 percent, given expectations of renewed confidence and political stability, underpinned by the strengthening of the economic recovery in developed economies. Appropriately managing domestic pressures in order to gain from the improved global economic environment will help maintain macroeconomic stability. Enhancing regional integration will also enable Cambodia to benefit more from the growth dynamics throughout the Association of Southeast Asian Nations (ASEAN) region. While Cambodia does have some fiscal space to increase wages, a cautious and careful approach to pay raise may work best.